On focus marking and predication. Evidence from Polish with some notes on Hausa - Tajsner, Przemysław (Lingua Posnaniensis, 2015)
The primary aim of the paper is to provide a new, derivational analysis of two types of Polish sentences with the occurrence of a particle to, which syntactically code focus and topic. These are: to-clefts (To Janek napisał list. ‘It was Janek who wrote the letter’), and topic-to sentences (Janek to napisał list. ‘As for Janek, he wrote the letter’). The secondary aim is to reflect on the relevance of the isomorphism of focus markers and non-verbal copulas in Polish with some reference to Hausa. Method: The approach follows a minimalist method but departs from cartographic accounts with dedicated heads in sentence left-periphery. Instead, it postulates that focus and topic are interpretive byeffects of Specification Predication. In this, the paper extends and modifies Kiss’s (2006, 2010) central idea that focusing is predication. Result & Conclusion: The account proves successful in explaining a few syntactic constraints, doing so in a simple, unitary fashion. Viewing focus as a derivative of predication is a step towards understanding the relation between narrow syntax and information structure.